Similarity level of Nepenthes spp. based on the qualitative characters - Putri Lukmanasari; Aziz Purwantoro; Rudi Hari Murti; Zulkifli Zulkifli (Jurnal Ilmu Pertanian, 2020)
Nepenthes, also known as pitcher plant, are unique and interesting flora developed as ornamental plants. This species has an attraction not only on the flowers but also on the diverse shapes and colors of the pitchers. Each Nepenthes species and hybrid has a variety of characters. The genetic relationship and diversity in Nepenthes species and hybrids can be determined based on the morphological characterization. The purpose of this study was to determine the similarity level among the Nepenthes accessions based on 31 qualitative characters. In this study, 30 Nepenthes species and 11 hybrids were used. The range of the similarity coefficient of Nepenthes species was 0.28-0.65, and divided into two major groups namely group A and B. Group A was the Nepenthes population which had petioles consisted of 17 accessions, while group B had folius consisting of 24 accessions. It indicated that when the similarity value is higher, the similarity level between each plant becomes higher. Principle Coordinates Analysis (PCoA) provided an overview of the relationship among the genotypes in coordinates. Species with a high similarity coefficient were in a close position, whereas species with a low similarity coefficient were in a remote position. Based on the PCoA, the species were grouped based on the similar characters, which was supported by the dendrograms.